2020
DOI: 10.3390/ht9010001
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Next Generation Sequencing to the Analysis of Familial Breast/Ovarian Cancer

Abstract: Next generation sequencing (NGS) provides a powerful tool in the field of medical genetics, allowing one to perform multi-gene analysis and to sequence entire exomes (WES), transcriptomes or genomes (WGS). The generated high-throughput data are particularly suitable for enhancing the understanding of the genetic bases of complex, multi-gene diseases, such as cancer. Among the various types of tumors, those with a familial predisposition are of great interest for the isolation of novel genes or gene variants, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 86 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…The evaluation of microarray-based gene expression is one of the most frequently utilized high-throughput and thriving approaches which is used to analyze the complex disease pathogenesis [ 8 ]. Although the researches which were carried out used human ovarian cancer gene expression profiling were rarely found, there have been technologies formed which yield high-throughput so as to determine new biomarkers and therapeutic targets in various types of cancers incorporating the ovarian cancer [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of microarray-based gene expression is one of the most frequently utilized high-throughput and thriving approaches which is used to analyze the complex disease pathogenesis [ 8 ]. Although the researches which were carried out used human ovarian cancer gene expression profiling were rarely found, there have been technologies formed which yield high-throughput so as to determine new biomarkers and therapeutic targets in various types of cancers incorporating the ovarian cancer [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…High throughput technologies have been developed to identify novel biomarkers and therapeutic targets in different types of cancers including ovarian cancer. [6][7][8] Winterhoff et al, used the single cell sequencing and demonstrated the heterogeneity within ovarian cancer epithelium and cancerrelated stromal cells. 9 Zhang et al, performed next-generation sequencing-based genomic profiling analysis and identified novel mutations for clinical diagnosis in Chinese primary epithelial ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the risk to miss large deletions and complex rearrangements during the analysis should be taken into consideration [21,37]. It is predicted that this kind of issues would be overcome in a close future with novel artificial intelligence supported NGS sequencing platforms providing very dynamic and specific sequencing data with more information, higher quality and lower costs [36]. At the moment, however, the capacity in generating sequencing data is consistently higher than the possibility of the medical community (oncologists, geneticists, biologists) to interpret the generated data and to understanding the biological and clinical significance that guide the decision-making process.…”
Section: Caucasianmentioning
confidence: 99%